2022
DOI: 10.3390/genes13020181
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Root System Architecture in Maize

Abstract: Roots are important plant organs for the absorption of water and nutrients. To date, there have been few genome-wide association studies of maize root system architecture (RSA) in the field. The genetic basis of maize RSA is poorly understood, and the maize RSA-related genes that have been cloned are very limited. Here, 421 maize inbred lines of an association panel were planted to measure the root systems at the maturity stage, and a genome-wide association study was performed. There was a strong correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Nitrogen stress is a major limiting factor for crop production worldwide, and plant RSA is of great significance in nutrient stress tolerance [ 39 ]. In recent years, the use of RSA is predicted to result in a “second green revolution” in agriculture [ 13 , 40 ]. Different phenotyping methodologies for early crops’ RSA screening were used, expecting that genotypes with diverse root architecture at the seedling stage would respond similarly at the adult stage when water and/or nutrients became limited for grain yield [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen stress is a major limiting factor for crop production worldwide, and plant RSA is of great significance in nutrient stress tolerance [ 39 ]. In recent years, the use of RSA is predicted to result in a “second green revolution” in agriculture [ 13 , 40 ]. Different phenotyping methodologies for early crops’ RSA screening were used, expecting that genotypes with diverse root architecture at the seedling stage would respond similarly at the adult stage when water and/or nutrients became limited for grain yield [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results provide an important strategy to develop high-quality varieties in maize breeding program. A total of 63 loci and 189 candidate genes associated with root system architecture in maize were identified by Wu et al [22] using GWAS analysis. This GWAS analysis performed by using 1.25 million SNPs and 421 maize inbred lines.…”
Section: Resultsmentioning
confidence: 99%
“…Right now, GWAS have been widely used to detect the genomic regions correlated with the complex traits in human, animals, and plants. In plants, GWAS have been detected many genes associated to the complex traits, such as in Arabidopsis, rice, maize, sorghum, wheat, barley, and many other plants [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Phenotypic data and genome-wide genotypes are required in GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…Because LD often involves a relatively broad region surrounding each significant locus, candidate genes often remain unknown. Several previous studies suggested that integrating GWAS results and gene expression data is a powerful way to detect candidate genes [ 33 , 54 , 55 , 56 ]. In the current study, the integration of GWAS and DEG data led to the identification of 48 candidate genes.…”
Section: Discussionmentioning
confidence: 99%